Implementation Of the School Literature Program to Grow a Reading Culture of Students at Junior High School Demak Regency - Irsiyantono, Devyandi Nur; Subyantoro, Subyantoro; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The implementation of the School Literacy Movement (GLS) in SMP Kabupaten Demak is suspected to have not been optimal. This study aims to evaluate the context, inputs, processes, products, and outcomes of the GLS program at SMP Kabupaten Demak. This research is evaluative research. Data were collected by interview, observation, questionnaire, and document study methods. Data analysis was carried out using an interactive model technique. The results of the context evaluation show that SMP Negeri 1 Demak has contextual aspects that support synergies with the GLS program. This has not been done optimally by SMP Negeri 1 Karangtengah and SMP PGRI 1 Demak. The input evaluation shows that SMP Negeri 1 Demak already has good input aspects, as well as SMP Negeri 1 Karangtengah is inversely proportional to SMP PGRI 1 Demak which is still lacking. The results of the process evaluation show that the program has been running well in SMP Negeri 1 Demak, SMP Negeri 1 Karangtengah and SMP 1 PGRI Demak is still not optimal. The results of the product evaluation based on the results of the KEM test concluded that SMP Negeri 1 Demak was more dominant in the medium category 111-149 Kpm (words per minute) as much as 31%, SMP 1 Karangtengah was more dominant in the slow category students 72-110 Kpm as much as 32%, and SMP PGRI 1 Demak is more dominant with students in the 72-110 Kpm slow category as much as 47%. Outcome evaluation shows that the GLS provides a change in the attitudes of students and teachers.